The effectiveness of community action in reducing risky alcohol consumption and harm: a cluster randomised controlled trial. - Anthony Shakeshaft; Christopher Doran; Dennis Petrie; Courtney Breen; Alys Havard; Ansari Abudeen; Elissa Harwood; Anton Clifford; Catherine D'Este; Stuart Gilmour; Rob Sanson-Fisher (PLoS Medicine, 2014)
Background The World Health Organization, governments, and communities agree that community action is likely to reduce risky alcohol consumption and harm. Despite this agreement, there is little rigorous evidence that community action is effective: of the six randomised trials of community action published to date, all were US-based and focused on young people (rather than the whole community), and their outcomes were limited to self-report or alcohol purchase attempts. The objective of this study was to conduct the first non-US randomised controlled trial (RCT) of community action to quantify the effectiveness of this approach in reducing risky alcohol consumption and harms measured using both self-report and routinely collected data. Methods and findings We conducted a cluster RCT comprising 20 communities in Australia that had populations of 5,000-20,000, were at least 100 km from an urban centre (population ≥ 100,000), and were not involved in another community alcohol project. Communities were pair-matched, and one member of each pair was randomly allocated to the experimental group. Thirteen interventions were implemented in the experimental communities from 2005 to 2009: community engagement; general practitioner training in alcohol screening and brief intervention (SBI); feedback to key stakeholders; media campaign; workplace policies/practices training; school-based intervention; general practitioner feedback on their prescribing of alcohol medications; community pharmacy-based SBI; web-based SBI; Aboriginal Community Controlled Health Services support for SBI; Good Sports program for sports clubs; identifying and targeting high-risk weekends; and hospital emergency department-based SBI. Primary outcomes based on routinely collected data were alcohol-related crime, traffic crashes, and hospital inpatient admissions. Routinely collected data for the entire study period (2001-2009) were obtained in 2010. Secondary outcomes based on pre- and post-intervention surveys (n = 2,977 and 2,255, respectively) were the following: long-term risky drinking, short-term high-risk drinking, short-term risky drinking, weekly consumption, hazardous/harmful alcohol use, and experience of alcohol harm. At the 5% level of statistical significance, there was insufficient evidence to conclude that the interventions were effective in the experimental, relative to control, communities for alcohol-related crime, traffic crashes, and hospital inpatient admissions, and for rates of risky alcohol consumption and hazardous/harmful alcohol use. Although respondents in the experimental communities reported statistically significantly lower average weekly consumption (1.90 fewer standard drinks per week, 95% CI = -3.37 to -0.43, p = 0.01) and less alcohol-related verbal abuse (odds ratio = 0.58, 95% CI = 0.35 to 0.96, p = 0.04) post-intervention, the low survey response rates (40% and 24% for the pre- and post-intervention surveys, respectively) require conservative interpretation. The main limitations of this study are as follows: (1) that the study may have been under-powered to detect differences in routinely collected data outcomes as statistically significant, and (2) the low survey response rates. Conclusions This RCT provides little evidence that community action significantly reduces risky alcohol consumption and alcohol-related harms, other than potential reductions in self-reported average weekly consumption and experience of alcohol-related verbal abuse. Complementary legislative action may be required to more effectively reduce alcohol harms. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12607000123448.